Identyfikacja, ewidencja i prezentacja wyników działań proekologicznych w rachunku ekonomicznym - Węgrzyńska, Małgorzata (Identification and Presentation Effects of Ecological Activity in Economy Account, 2007)
This article describes a new conception of accounting - an environmental accounting and the financial statement based on three documents prepared by the ISAR. The aim of this article is a presentation of the problem as identyfication, recording, measuring events related with ecological activity. In this article, the author underlines the need to introduce standards that will describe ecological activity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 173-179